A low‐light image enhancement method based on bright channel prior and maximum colour channel. Issue 8 (26th February 2021) - Sandoub, Ghada; Atta, Randa; Ali, Hesham Arafat; Abdel‐Kader, Rabab Farouk
Abstract: Low‐light image enhancement algorithms have been introduced to improve the visual quality of low‐light images that may degrade the performance of many computer vision and multimedia systems designed for high‐quality images. However, the existing bright channel prior and maximum colour channel enhancement algorithms introduce halo artifacts and colour distortions while enhancing the images. To overcome these limitations, in this paper, an effective fusion‐based low‐light image enhancement algorithm is proposed. In the proposed algorithm, the illumination of the low‐light image is estimated from both the bright and maximum colour channels to overcome the halo artifacts and colour distortion problems. Further, an effective refinement method is utilized to improve the sharpness of the initial enhanced image representing the scene reflectance. Experiment results show that the proposed algorithm outperforms the state‐of‐the‐art algorithms qualitatively and quantitatively. Moreover, the proposed algorithm reduces the halo artifacts and colour distortion and enhances the details while preserving the naturalness.